Accumulation of pre-tRNA splicing '2/3' intermediates in a Saccharomyces cerevisiae mutant. - Ho, C K (1990)
In an effort to identify genes involved in the excision of tRNA introns in Saccharomyces cerevisiae, temperature-sensitive mutants were screened for intracellular accumulation of intron-containing tRNA precursors by RNA hybridization analysis. In one mutant, tRNA splicing intermediates consisting of the 5' exon covalently joined to the intron ('2/3' pre-tRNA molecules) were detected in addition to unspliced precursors. The mutant cleaves pre-tRNA(Phe) in vitro at the 3' exon/intron splice site, generating the 3' half molecule and 2/3 intermediate. The 5' half molecule and intron are not produced, indicating that cleavage at the 5' splice site is suppressed. This partial splicing activity co-purifies with tRNA endonuclease throughout several chromatographic steps. Surprisingly, the splicing defect does not appreciably affect cell growth at normal or elevated temperatures, but does confer a pseudo cold-sensitive phenotype of retarded growth at 15 degrees C. The mutant falls into the complementation group SEN2 previously defined by the isolation of mutants defective for tRNA splicing in vitro [Winey, M. and Culbertson, M.R. (1988) Genetics, 118, 609-617], although its phenotypes are distinct from those of the previous sen2 isolates. The distinguishing genetic and biochemical properties of this new allele, designated sen2-3, suggests the direct participation of the SEN2 gene product in tRNA endonuclease function.